Development of an injection molded ethylene-vinyl acetate copolymer (EVA) intravaginal insert for the delivery of progesterone to cattle - Cappadoro, Alejandro Jose (2015)
The purpose of this study was to develop a new injection-molded intravaginal insert man-ufactured from ethylene-vinyl acetate containing progesterone for a 7-day insertion periodin cattle. The manufacturing process resulted in a reduction in the residual drug comparedto the silicone insert available while still maintaining biological performance.